Personal, social, and environmental factors associated with lifejacket wear in adults and children: A systematic literature review - Peden, A.; Demant, D.; Hagger, Martin; Hamilton, K. (Public Library of Science, 2018)
Objective: Drowning claims 7% of the global burden of injury-related deaths. Lifejackets are routinely recommended as a drowning prevention strategy; however, a review of related factors regarding lifejacket wear has not previously been investigated. Methods: This systematic review examined literature published from inception to December 2016 in English and German languages. The personal, social, and environmental factors associated with lifejacket wear among adults and children were investigated, a quantitative evaluation of the results undertaken, and gaps in the literature identified. Results: Twenty studies, with sample sizes of studies ranging between 20 and 482,331, were identified. Fifty-five percent were cross-sectional studies. All studies were scored IV or V on the Australian National Health and Medical Research Council (NHMRC) grading system indicating mostly descriptive and cross-sectional levels of evidence. Factors associated with increased wear included age (mostly children), gender (mostly female), boat type (non-motorised), boat size (small boats), role modelling (children influenced by adult lifejacket wear), and activity (water-skiing, fishing). Factors not associated or inconsistent with lifejacket wear included education, household income, ethnicity, boating ability, confidence in lifejackets, waterway type, and weather and water conditions. Factors associated with reduced lifejacket wear included adults, males, discomfort, cost and accessibility, consumption of alcohol, and swimming ability. Three studies evaluated the impact of interventions. Conclusion: This review identified factors associated with both increased and decreased lifejacket wear. Future research should address the motivational factors associated with individuals’ decisions to wear or not wear lifejackets. This, combined with further research on the evaluation of interventions designed to increase lifejacket wear, will enhance the evidence base to support future drowning prevention interventions.